ANALISIS KUALITATIF TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS 3 SD DI KECAMATAN PURWAKARTA KABUPATEN PURWAKARTA - Afina Nuryati Rachman, - (2020)
Kemampuan koneksi matematis penting dimiliki siswa. Penelitian ini bertujuan untuk mengetahui kemampuan koneksi matematis siswa kelas 3 di Kecamatan Purwakarta dalam menyelesaikan materi Sudut dan Pengukuran Tidak Baku berdasarkan indikator kemampuan koneksi NCTM yang sudah seharusnya diketahui oleh pendidik. Penelitian dilakukan kepada 9 siswa kelas 3 di SDN 10 Nagri Kaler, Kecamatan Purwakarta, terdiri dari 3 siswa berkemampuan lower-thinker, 3 siswa berkemampuan middle-thinker, dan 3 siswa berkemampuan higher-thinker. Metode yang digunakan ialah penelitian deskriptif dengan pendekatan kualitatif. Metode pengumpulan data yang digunakan adalah observasi, tes tertulis, wawancara dan dokumentasi dengan instrument pengumpulan data yaitu observasi tidak terstruktur, soal kemampuan koneksi matematis, dan pedoman wawancara. Hasil penelitian menunjukkan bahwa kemampuan koneksi matematis 9 siswa kelas 3 SDN 10 Nagri Kaler dalam menyelesaikan soal sudut dan satuan pengukuran tidak baku masuk dalam kategori kemampuan koneksi matematis sedang dengan mencapai 8 indikator, 1 siswa masuk ke dalam kategori rendah, 5 siswa masuk ke dalam kategori sedang, dan 3 orang siswa masuk ke dalam kategori tinggi pada indikator kemampuan koneksi matematis. Students' mathematical connection ability is considered as one of the abilities that must be possessed by students. Students' mathematical connection abilities are often not in harmony with general mathematical abilities. The ability of students' mathematical connections should be known especially by the teacher in preparation for learning. This study aims to determine the mathematical connection ability of grade 3 students in Purwakarta 2019/2020 academic year in completing material Corner and Unstandard Measurement Unit based on indicators of connection ability of the National Council of Teachers of Mathematics. This research was conducted on 9 grade 3 students at SDN 10 Nagri Kaler, Purwakarta, Purwakarta Regency. The 9 students consisted of 3 students with lower-thinker abilities, 3 students with middle-thinker abilities, and 3 students with higher-thinker abilities. The research method used is descriptive research method with a qualitative approach. Data collection methods in this study used observation, written tests of mathematical connection ability of angular material and nonstandard measurement units, and student interviews with data collection instruments namely unstructured observation, about mathematical connection ability, and interview guidelines. The results showed that the mathematical connection ability of 9 grade 3 students of SDN 10 Nagri Kaler in solving problems of angles and nonstandard measurement units was included in the category of moderate mathematical connection capabilities by reaching 8 indicators, 1 student entered into the low category, 5 students entered into the category medium, and 3 students fall into the high category on the indicator of mathematical connection ability.